Detection of lead, cadmium and nickel in children’s plastic toys using atomic absorption spectroscopy (AAS) - Hashim, Hazirah (Universiti Sains Malaysia, 2025)
Exposure to heavy metals present in plastic toys which can pose significant health risks to children is a growing concern particularly through mouthing behaviours like chewing, licking and sucking. The contents of three heavy metals (Pb, Cd and Ni) were analysed in six children’s plastic toys samples by using atomic absorption spectrosocpy (AAS). The plastic toy samples were prepared using dry ashing method and digested with nitric acid and hydrogen peroxide. The analysis showed that all six plastic toy samples contained Cd (0.2026 - 3.5519 mg/kg), five out of six samples contained Ni (0.5581 - 6.8927 mg/kg) and only one sample contained Pb (3.4529 mg/kg). All heavy metal concentrations were below the permissible limits specified in the EN71-3:2019 set by the European Union (EU). Leaching of Pb, Cd and Ni from plastic toy samples was conducted on the plastic toy samples under two different temperature conditions: room temperature and 50°C. Samples exposed to 50°C for four hours exhibited increased levels of Pb, Cd and Ni compared to unheated samples, demonstrating that elevated temperatures facilitated heavy metal leaching from plastic toys. Despite this, the leaching rates remained within the EU limits. These findings emphasised the potential risks of storing plastic toys in high-temperature environments, such as inside vehicles under direct sunlight for extended periods. While the tested toys were deemed safe for children, proper storage practices were strongly recommended.